Designing Synchronous Online Learning and Teaching Lab: An Online Professional Development Program to Foster the Technical and Social Competences of Synchronous Online Teachers - Maaike Grammens; Fien De Smedt; Bram De Wever (Education Sciences)
Synchronous Online Teaching (SOT) is becoming increasingly popular, but research shows many teachers are inadequately prepared, calling for greater investment in professional development (PD). Additionally, there is a significant gap in research systematically describing the design of evidence-based PD initiatives. Consequently, researchers and educators lack an understanding of the essential components of these interventions, which obstructs the replication, dissemination, and implementation of evidence-based PD programs for synchronous online teachers. This study presents the design of SOL-lab, an online PD program aimed at fostering teachers’ technical and social SOT competences. A detailed overview of the online PD design is offered, encompassing the underlying theoretical and empirical foundations, macro-level design principles, and micro-level instructional and learning activities. More particularly, three key design principles guided the online PD development process: focused observation of SOT, providing and receiving feedback, and stimulating the transfer of learning. By integrating authentic learning experiences and fostering reflective practice, our program aims to empower teachers with the necessary competences to thrive in SOT environments. An analysis of teachers’ perceptions indicates that they had a positive experience with the effective features of the PD program. This study offers valuable insights for the development of effective online PD initiatives for SOT.